Strategy for Improving the Performance of State Civil Apparatus in the Era of Digitalization (Study at the Malang State Property and Auction Service Office) - Wahyu Kurniawan Permadi; Muhammad Wahyu Prasetyo Adi; Thavia Aisyah Shinta Aprilla (PERSPEKTIF, 2025)
This study aims to analyze the strategies used by the KPNL Malang agency to improve the performance of the state civil apparatus in the digitalization era. The research used qualitative research methods. The results showed that improving Apparatus performance at KPKNL Malang was analyzed from 3 variables, namely: (1) continuous improvement, implementation of FWS (flexible working space) based on the circular letter of the Minister of Finance Decree Number 223/KMK.01/2020 concerning Implementation of Workplace Flexibility (FWS) within the Ministry of Finance. (2) To improve the quality of results, internally, the KPKNL Malang agency uses the e-peform performance reporting application, and externally, KPKNL Malang opens more channels for public complaints through online channels and social media openly accessible on the official KPKNL Malang account. (3) human resource development: In increasing the capacity of the Apparatus, the KPKNL Malang agency requires completing 20 training hours/per year for each Apparatus, which can be pursued through offline training at the training centre or online / independently in the KLC application.